Dinamika Keindependensian KPK pasca putusan Mahkamah Konstitusi Nomor 36PUU-XV2017 - Aprilia, Fatimah (Faculty of Law, Universitas Riau, 2024)
Knowing the dynamics of the KPK’s independence after the Constitutional Court decision Number 36/PUU-XV/2017 is the aim of this research. Apart from that, the aim of Knowing the dynamics of the KPK’s independence after the Constitutional Court decision Number 36/PUU-XV/2017 is the aim of this research. Apart from that, the aim of establishing an independent KPK institution is to create a government free of corruption and limit the excessive reach of executive power. The findings of this research clarify how the KPK is positioned as a state institution based on Constitutional Court Decision Number 36/PUU-XV/2017 which places it under the executive branch of government. This raises problems with institutional relations within the KPK. Therefore, the DPR’s right to inquiry submitted to the Corruption Eradication Committee is an implementation of the legislative oversight role carried out by the executive agency. Apart from that, this decision is the basis for changes to the KPK Law which reaffirms the position of the KPK as a state executive institution. In relation to the Corruption Eradication Commission and political power, it would be better if the members themselves chose the Chairman of the Corruption Eradication Commission rather than the DPR.